Fertilisasi in Vitro dari perspektif Hukum, Biologi dan Moral Katolik - Sembiring, Anita Anastasya Br (IN VERITATE LUX, 2024)
In vitro fertilization (FIV) is a complex and controversial topic that has attracted attention in various fields of research, including law, biology, and ethics. This article outlines the results of desk research that describes FIV from various perspectives, particularly within the framework of Catholic law, biology, and morals. This article presents an in-depth analysis of FIV from the perspectives of Catholic law, biology, and morals. It also identifies various ethical challenges and questions associated with FIV and proposes solutions that can honor Catholic moral principles while taking into account the legal framework and relevant biological concepts. In the face of these complex debates, a collaborative effort between legal experts, biological scientists, and Catholic theologians may be necessary to seek the best path that best accommodates all these perspectives. Key words: In Vitro Fertilization, Law, Biology, Catholic Moral, Pastoral